دراسة وبائية لنسب الإصابة بالبروسيلا في محافظة ميسان - مريسل عباس جلوب (University of Thi-Qar Journal of Science, 2013)
World health organization (WHO) referred there were more than half and million person infected withbrucellosis in the world, and this number may be increased in the future. In Iraq the brucellosis consideredendemic disease in human and animals in spite of the measure steps that applied to control on the disease.The study was performed to obtain the information about the disease from aspect: Ages, Regions,Months of infection, commonest clinical symptoms.The data were collected from (266) patients of bothsexes in period between (First June-2010 to First June-2011) and the disease was diagnosed according to theclinical signs and symptoms and using Rose Bengal test in AL-Sadder Hospital.The high percent of thedisease were recorded in females 143(53.75%),while the males were recorded in percent 123(46.24%). Thehigh percent of the disease were recorded in ages between (31-40)years in percentage 88(33.08%),followed by the ages between (21-30) years in percentage 72(27.06%).The disease was increased in months of springand first of the summer (March, April, May ,June) in percentage 43(16.16% ) , 34(12.68%), 29(10.90%),21(8.8%) respectively. Amara district was the commonest region for infected with brucellosis in percent100 (37.59%), followed by Kumait district in percent 55(20.67%).